Application of fourth industrial technologies: a case of Zimbabwe's mines - Alouis Chilunjika (Insights into Regional Development)
The Fourth Industrial Revolution (4IR) dispensation has revolutionised mining activities globally. New technologies and automation, among others, have been introduced into the exploration, quarrying, mining and extraction of minerals in underground and open pit mining in developing countries like Zimbabwe. However, some impediments exist to adopting and operationalising 4IR technologies in Zimbabwe's mining sector. In light of this, the study examines the challenges and prospects underpinning the adoption and operationalisation of 4IR technologies in Zimbabwe's mining sector. Due to its qualitative nature, the study was based on a thorough examination of textual materials that were specifically chosen, including books, newspaper articles, government publications, journal articles, and book chapters. The study purposively selected Zimplats Mine, Unki Mine, Murowa Diamonds, Mimosa Mine, Freda Rebecca Mine and Caledonia Mining Group as the units of analysis. The obtained data was examined by applying content and thematic analysis methods. According to the study, various mining companies in Zimbabwe use various 4IR technologies in their respective mining activities, such as automated drilling and loading systems, digital twin technology, Internet of Things (IoT) devices and remote sensing, artificial intelligence (AI)-driven data analytics, automation, machine learning, and cloud computing, at varying degrees and stages. These technologies are crucial in enhancing productivity, efficiency, safety, decision making and cost reduction in Zimbabwe's mining sector. However, the study established that the implementation and adoption of 4IR technologies in Zimbabwe's mining sector needs to be improved because of a lack of capital, the absence of digital infrastructure, resource immobility, and the unavailability of necessary talent and skills, among others. To address the identified challenges, the study recommended that there is a need for the development of 4IR infrastructure, enactment and strengthening of 4IR supporting policy and regulatory frameworks, capacity building and training, collaborations and partnerships, supporting research and development (R&D) initiatives, and awareness campaigns and stakeholder engagement.